Gangguan Berbahasa Anak Sumbing pada Tokoh Ame dalam Film Serdadu Kumbang: Penelitian - Nurfalida; Husna Rifdah; Sundawati Tisnasari (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe the form of language disorders experienced by children with cleft lip conditions, through an analysis of the figure Ame in the film Serdadu Kumbang. The character Ame realistically depicts a child with a cleft lip who faces challenges in pronouncing words correctly. This researcher applies a descriptive qualitative method with a psycholinguistic approach. Information was obtained by observing and recording Ame's dialogues shown in the film on the YouTube channel. The results of the study indicate that Ame faces various articulation disorders, especially in consonant sounds. This results in distortion or changes in word pronunciation, for example the word